POLICY PAPER: GROWTH POLICY - Hare or Tortoise? Productivity and Growth of Irish Domestic Firms - Lawless, Martina (The Economic and Social Review, 2025)
Over 20 years ago, Honohan and Walsh (2002) unravelled the key drivers behind the dramatic growth of the Irish economy after decades of underperformance. The role of multinationals was a critical element in the convergence with other EU Member States. Even at this stage, however, multinational activity was causing challenges for measurement of the overall economy. Since then, multinational activity has boomed in Ireland and so too have the difficulties their activities pose for understanding how the domestic side of the economy is performing. This paper presents a range of indicators of structure and performance of the domestic side of the Irish economy alongside comparisons with the multinational sector and also with comparator countries. It finds that although there has been steady growth amongst the domestically-dominated sectors, productivity gaps and potential crowding-out remain concerns.